IGF-1 c.258 A > G synonymous mutation ameliorates senile osteoporosis - Zhaoguo Wang; Dayou Dai; Siyao Wang; Libo Zhang; Yi Li; Xunming Zhang; Yunyun Cheng; Linlin Hao (Communications Biology)
Abstract Senile osteoporosis (SOP) is a multifactorial, age-related progressive phenomenon with a considerable morbidity and mortality. IGF-1 is an important regulator of bone reconstruction and metabolism throughout life. Nevertheless, our previous study unexpectedly found there is no change in the peak bone mass with a altered IGF-1 gene expression leaded by IGF-1 c.258 A > G synonymous mutation. Considering its involvement in the cellular senescence, we suspected c.258 A > G may participate in SOP. Therefore, the effect of IGF-1 c.258 A > G on SOP was firstly detected, the changes of bone formation and bone resorption index in SOP mice with two genotypes indicated it improved SOP. Then, the in vitro study confirmed the mutation ameliorates SOP by promoting the growth and development of senescent osteoblasts. At last, co-culture of osteoblast and osteoclast further verified the mutation prevents SOP by increasing the bone formation capacity of senescent osteoblasts. Collectively, this study illuminated the role of IGF-1 c.258 A > G in ameliorating SOP.